Lights in Portugal: update of a debate (Revista Angelus Novus, 2011)
The historian Flávio Rey de Carvalho reconstructs the debate about the existence or not of the Lights in Portugal, making approximations between the movement of ideas in different European nations, in order to question the pejorative value generally attributed by historiography to the seven hundred Portuguese. The author suggests the validity of using the expression “Portuguese Enlightenment”.